2016
DOI: 10.3233/jad-151071
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory Performance in Alzheimer’s Disease Depends on Retrieval Frequency

Abstract: Alzheimer's disease (AD) is characterized by memory disturbances primarily caused by pathogenic mechanisms affecting medial temporal lobe structures. As proposed by current theories of memory formation, this decrease is mediated by the age of the acquired knowledge. However, they cannot fully explain specific patterns of retrograde amnesia in AD. In the current study we examined an alternative approach and investigated whether the extent and severity of retrograde amnesia in AD is mediated by the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Furthermore, recent evidence supports multiple trace theory (MTT), according to which semantic memory retrieval is independent from the hippocampus and mediated by the neocortex after a certain consolidation period (Moscovitch et al, 2005a), while episodic retrieval is subserved by medial temporal lobe/hippocampus regardless of the lifetime period of acquisition (Moscovitch et al, 2005b). For example, the presence of a temporal gradient is more consistent for episodic memory (Philippi et al, 2012), including vividness and details specificity (Donix et al, 2010;Irish et al, 2011b;Seidl et al, 2011;Müller et al, 2016), while personal semantics can be relatively preserved in AD (Martinelli et al, 2013). Moreover, it has been suggested that the degree of impairment of semantic ABM may depend on the stage of the disease.…”
Section: The Remote Self In Admentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, recent evidence supports multiple trace theory (MTT), according to which semantic memory retrieval is independent from the hippocampus and mediated by the neocortex after a certain consolidation period (Moscovitch et al, 2005a), while episodic retrieval is subserved by medial temporal lobe/hippocampus regardless of the lifetime period of acquisition (Moscovitch et al, 2005b). For example, the presence of a temporal gradient is more consistent for episodic memory (Philippi et al, 2012), including vividness and details specificity (Donix et al, 2010;Irish et al, 2011b;Seidl et al, 2011;Müller et al, 2016), while personal semantics can be relatively preserved in AD (Martinelli et al, 2013). Moreover, it has been suggested that the degree of impairment of semantic ABM may depend on the stage of the disease.…”
Section: The Remote Self In Admentioning
confidence: 81%
“…Interestingly, it has been reported that remote memories are proportionally more frequently retrieved by people with AD (De Simone et al, 2016;Müller et al, 2016) and that detail specificity is positively associated to retrieval frequency of memories (Müller et al, 2016). Hence, retrieval frequency may modulate vividness and temporal gradient effects, as a result of the semanticisation process of more frequently retrieved memories, which would gradually acquire independence from medial temporal structures.…”
Section: The Remote Self In Admentioning
confidence: 99%
“…32(8), 906-919. DOI: 10.1037/neu0000486 6 1989; Leyhe, Müller, Milian, Eschweiler & Saur, 2009;Müller, Mychajliw, Reichert, Melcher & Leyhe, 2016). A few studies using the AMI have failed to find statistically significant effects, but report numerical differences in the same directions (Addis & Tippet, 2004;Gilboa et al, 2005;Meeter, Eijsackers & Mulder, 2006;Nestor, Graham, Bozeat, Simons & Hodges, 2002).…”
Section: The Life Span Distribution Of Autobiographical Memory In Alzmentioning
confidence: 99%
“…It can be argued that representations of personally relevant knowledge that became part of semantic memories earlier in life are more strongly integrated in the brain, better consolidated, and therefore, less degraded by AD [ 19 ]. The episodic memory findings suggest that the more frequently retrieved autobiographical memories generally become more independent from the hippocampal complex, and might thus be better protected from early hippocampal damage related to AD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%